Effects of Treated Greywater on Mineral Contents and Proximate Compositions of Pepper Fruits - Femi Alao; Ajayi Johnson Oloruntade; Adewoye Alade Olanipekun; Afolabi Matthew Oke; Oluwatosin Onaopemipo Olofintoye; Daniel Uwumarogie Idusuyi; Opeyemi Bayode; Suzie Eyenuro (ABUAD Journal of Engineering Research and Development, 2025)
This study investigates the effects of treated greywater on the mineral and proximate compositions of pepper grown in Akure, Nigeria. Greywater was treated using a filtration system including sand and gravels with common reed, to remove contaminants and reduce potential health risks. The treated greywater was then used to irrigate pepper plants. Minerals and proximate analysis were conducted on the fresh pepper fruits. For 2016, 2017 and 2018 dry seasons, samples from treated greywater irrigation plots showed nitrogen (N) values of 0.37, 0.37, and 0.37 mg/kg, phosphorus values of 0.10, 0.19, and 0.11 mg/kg, and potassium values of 129.00, 130.00, and 128.00 mg/kg, respectively. Samples from plots watered with treated greywater also had 2.30, 2.26, and 2.28% protein, 1.36, 1.41, and 1.38% fat, and 2.00, 3.15, and 3.06% carbohydrates in the dry seasons of 2016, 2017, and 2018, respectively, based on the proximate analysis of hot pepper. These also indicate that irrigation with treated greywater can significantly enhance food supplements needed for human growth and does not affect the quality of pepper for human consumption. Notably, no significant accumulation of heavy metals was detected in the fruits. Continued monitoring and optimized treatment processes are recommended to ensure long-term safety.